If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
25-((3/7)*x) = (4/7)*x+19 // - (4/7)*x+19
25-((3/7)*x)-((4/7)*x)-19 = 0
(-3/7)*x+(-4/7)*x-19+25 = 0
6-x = 0 // - 6
-x = -6 // * -1
x = 6
x = 6
| 2(s-4)-7=22 | | N/2=6 | | x+1=6x+11 | | 9x+5-4x=-2 | | (3x+4)(3x+4)=18 | | 3c-2(c-9)=2+2c | | 7x/8-2=x | | 6+(-82)-3= | | -3d-3=-15 | | 0.5x-0.3x-2=-6 | | 14x-48=13x-21 | | 4d+c-d= | | -8-6=12-10x | | 5/6x+18-1/6x=6 | | -34-2x=10x | | 20a^2-39a+18=0 | | -5/69= | | 3.3d=23.43 | | 2b^2-3=5b | | 3c-2c-18=2+2c | | 7(5x-72)= | | 5x^2-4x=-1 | | d/6=5 | | 1.9x+10-5.9x=2 | | 3c+3=-3 | | 4/7x=-12 | | 15-2x = 4 | | 9x+7.16=3x+17 | | 2x-3x-10=70 | | 2n^2+6=0 | | 15-2x = 4 | | 6i/4+2i |